Security Issues in Social Media: Challenges and Solutions - Mardin A. Anwer; Rina Dinkha Zarro; HamaAliFaraj, Kamaran HamaAli Faraj (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The popularity of social networking becomes very important for the societies. It makes life easy and modified the traditional society (TS) to electronical society (ES). Thus, community by using of social networking in every day is more than usual and becomes part of our daily life and without doubt sharing with our life and all around human daily activity helped by Facebook and it is a new way of 21 century communicates. The average use of social media by a normal person is seven hours per day. Social media users share ideas, information and communicate with different people. This communication reveals a lot of information such as private and business information that makes it visible to anyone who wants to view it or it become cross information. Cross information means seen and exchange both of users’ information. Subsequently, other people are intending to take advantage of this information. They can send spam or steal identities to sell it or use it for other purposes. This paper introduces new architecture to protect users’ accounts that can be use in Facebook. We also introduce some techniques that can be used in any types of social media networking. In addition, our proposed system architecture is increasing the security issue by using of two-tier architecture (2TA) authentication especially enhances user privacy in social website. The new contribution of our proposed system will insure no fraud account or fake identity is created in the network related to the business, as well as, people related to this account, all data and information will be kept private and less spam attacks will be guaranteed. In order to evaluate the proposed architecture tests, some profiles of academic staff and employees in the college of engineering–Salahaddin University were inspected.